Effect of the Cropping Year on the Quality of Winter Wheat - Sipos, Péter; Győri, Zoltán (Acta Agraria Debreceniensis, 2004)
We examined the formation of quality parameters of winter wheat in a small plot variety comparison experiment from four cropping years. Our aim was to estimate the year effect on several quality parameters of winter wheat.We established in relation to the distribution of precipitation of the examined years that the years 1997 and 2000 were behind the thirty year average typical precipitation of this site both in the case of the whole vegetation period and the spring and summer. It was unfavourable for qualitative wheat production. 1998 and 1999 were good for cropping considering the amount and distribution of rainfall.Examining the formation of quality parameters we found that the baking value was maximum in 1997, with a moderate amount of normal distributed rainfall for the examined varieties. The mid-late maturating varieties showed better baking value in drought years than in wet years. In the case of the wet gluten content, we established higher values after a rainier spring-summer period. There is a conspicuous difference between the falling number of extensive and intensive varieties and the year had significant effect on the formation of values. We established with correlation analysis that both the precipitation of vegetation period and the maturing rainfall had considerable effect on the value of falling number. Examining the effect of fertilization on the formation of wet gluten content as a quadratic equation, we found that precipitation may both increase and maximalize the value of this quality parameter.